Muscle Conduction Velocity Estimation Using High Density Electromyography - De, Ashmita; Johns, Gregg; Morin, Evelyn (CMBES Proceedings, 2016)
Overall conduction velocity (CV) in a population of activated muscle fibres is related to the state of the muscle and can be estimated from the electromyogram (EMG). CV estimation is affected by the distance between electrodes of a bipolar pair (inter-electrode distance or IED), and the distance between two bipolar pairs used to detect conduction delay (inter-signal distance or ISD). Reported CV’s are generally in the range of 3.5 – 5 m/s [Farina-MBEC-2001; Beck-JEK-2004]. The purpose of this study was to examine the effect on CV estimates of IED and ISD, contraction level, and muscle length. EMG data were recorded from the long and short heads of the biceps brachii (BBL and BBS), and brachioradialis (BR), of five subjects, using monopolar high-density EMG electrodes. Subjects performed elbow flexion contractions at three force levels (30, 40 and 50% maximum), and three elbow joint angles (60, 90 and 120 degrees). CV estimates were computed for different bipolar electrode configurations; estimates corresponding to published values were obtained for IED=15 mm and ISD=20 mm. ANOVA analysis of CV values revealed that contraction level had no significant effect (p-values: 0.336 to 0.774), and CV varied significantly with joint angle only for the highest contraction level in BBS (p=0.01). Values for all contraction levels were then grouped; ANOVA analysis showed that CV varied significantly with muscle (p<0.00002) for all joint angles. These results are analysed with regard to the nature of the EMG signal, and how the signal changes with contraction level and joint angle.